DONATE BLOOD, SAVE A LIFE (Ustozlar uchun, 2026)
This article highlights the critical importance of voluntary blood donation in modern medicine. Blood loss resulting from severe accidents or major surgeries can cause systemic oxygen starvation, leading to organ failure and fatal outcomes. While blood transfusions are vital for patient survival, contemporary medical practices frequently utilize specific components—such as plasma, platelets, or red blood cells—rather than whole blood. The paper outlines the essential eligibility criteria for donors, including age, weight, and health status, alongside standard donation procedures. Furthermore, it underscores the global impact of blood donation through the extraordinary case of James Harrison, the "Man with the Golden Arm," whose rare antibodies saved millions of infants, exemplifying how altruistic acts profoundly preserve human life.